Americanized : rebel without a green card - Saedi, Sara (Alfred A. Knopf, 2018)
Summary: In San Jose, California, in the 1990s, teenaged Sara keeps a diary of life as an Iranian American and her discovery that she and her family entered as undocumented immigrants.